Phenotypic and functional modulation of 20–30 year old dermal fibroblasts by mid- and late-gestational keratinocytes in vitro. Issue 5 (August 2015) - Wang, Zhe; Liu, Xiaoyu; Zhang, Dianbao; Wang, Xiliang; Zhao, Feng; Zhang, Tao; Wang, Rui; Lin, Xuewen; Shi, Ping; Pang, Xining
Highlights Mid-gestational KCs exert a positive effect on proliferation and migration in fibroblasts. Mid-gestational KCs exert a positive effect on collagen synthesis in fibroblasts. Mid-gestational KCs exert a positive effect on ECM remodeling in fibroblasts. The positive effect is mediated by a variety of molecules.